Analisis Nilai Cerita Rakyat Raden Aria Wirasaba Di Desa Adiarsa, Kecamatan Karawang Barat, Kabupaten Karawang - Nisa Aprianingsih; Ferina Meliasanti; Imam Muhtarom (Peneliti.net, 2023)
Folklore Raden Aria Wirasaba This study utilizes several expert opinions regarding the values ​​contained in folklore. This research uses a qualitative approach. The research method applies ethnographic methods. The results of the analysis of the value of the story of Raden Aria Wirasaba, found several values ​​including religious values ​​(religious relations with fellow human beings), moral values ​​(moral values ​​related to oneself and moral values ​​related to fellow human beings), cultural values ​​(cooperating, helping , compassion, harmony, and caring for the fate of others), social values ​​(fairness, cooperation, empathy, respect, sense of belonging, and mutual help), educational values ​​(values ​​of social education, values ​​of character education, and values ​​of heroism education), aesthetic value (moral beauty and moral beauty).